2023
DOI: 10.1186/s12936-023-04456-y
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and insecticide resistance in malaria vectors in Ellibou, southern Côte d’Ivoire and first finding of Anopheles arabiensis in Côte d’Ivoire

Abstract: Background Knowing the species composition and insecticide resistance status of the target vector population is important to guide malaria vector control. The aim of this study was to characterize the malaria vector population in terms of species composition, insecticide susceptibility status and potential underlying resistance mechanisms in Ellibou, southern Côte d’Ivoire. Methods A 1-year longitudinal entomological survey was conducted using ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…coluzzii with the former available in higher overall proportions and at most time points except in the middle of the dry season. This nding con rms several studies that have demonstrated that both species commonly occur in sympatry in West Africa, though they may differ substantially in their ecological behaviour, insecticide resistance status and vectorial capacity [45][46][47]. Previous entomological surveys in Benin have also shown a wide variability in the proportion of both sibling species in terms of geographical spread and seasons with reports of higher densities of An.…”
Section: Discussionsupporting
confidence: 83%
“…coluzzii with the former available in higher overall proportions and at most time points except in the middle of the dry season. This nding con rms several studies that have demonstrated that both species commonly occur in sympatry in West Africa, though they may differ substantially in their ecological behaviour, insecticide resistance status and vectorial capacity [45][46][47]. Previous entomological surveys in Benin have also shown a wide variability in the proportion of both sibling species in terms of geographical spread and seasons with reports of higher densities of An.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, this species has been found adapting in more polluted breeding sites associated with urbanization, unlike An. gambiae, which prefers small, temporary, sunlit, and clear freshwater pools, typical habitats found in rural areas (43,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%